Application of logical and mathematical methods for the analysis of environmental information - L. Sh. Akhmedova; A. A. Magomedova; R. T. Radjabova (Юг России: экология, развитие, 2022)
Aim. Evaluation of the possibilities of mathematical logic and logical‐mathematical methods in the description of complex natural systems in simple and clear constructions, as they act as a language, special research methods, a source of ideas and concepts in natural science.Discussion. The article discusses the possibilities and advantages of logical and mathematical methods in the analysis of natural science information, and, in particular, environmental data. It gives a comparative overview of logical and mathematical constructions in the formation of scientific thinking. The list of the most common mathematical and logical symbols for the formalised recording of complex ecological systems is provided, together with examples of the use of logical and mathematical formulas as formal and implicative statements in the brief recording of natural science information.Conclusion. The research conducted does not convincingly indicate unambiguous advantages of using the symbols of mathematical logic rather than verbal presentation. However, since ecology deals with the description of arch‐complex systems, including operations of formalised problem statement, the formalised structuring of ecosystems, the grouping of ecosystems according to measures of their similarity‐difference or inclusion–intersection, and the classification of selected ecosystems in a certain specified group, the need for widespread application of logical and mathematical research is indisputable.